Breakdown of species boundaries in Mandevilla: Floral morphological intermediacy, novel fragrances and asymmetric pollen flow - Rubini Pisano, María Aimé (2018)
Phenotypic intermediacy is an indicator of putative hybrid origin, and has provided the main clues to discovering hybrid plants in nature. Mandevilla pentlandiana and M. laxa (Apocynaceae) are sister species with clear differences in floral phenotype and associated pollinator guilds: diurnal Hymenoptera and nocturnal hawkmoths, respectively. The presence of individuals with intermediate phenotypes in a wild population raises questions about the roles of visual and olfactory signals (i.e. corolla morphology and floral fragrances) as barriers to interbreeding, and how the breakdown of floral isolation occurs.We examined phenotypic variation in a mixed Mandevilla population analysing the chemical composition of floral fragrances, characterizing floral shape through geometric morphometrics and assessing individual grouping through taxonomically relevant traits and an unsupervised learning algorithm. We quantified the visitation frequencies of floral visitors and tracked their foraging movements using pollen analogues.The presence of morphologically intermediate individuals and pollen analogue movement suggested extensive hybridization between M. laxa and M. pentlandiana, along with asymmetrical rates of backcrossing between these putative hybrids and M. laxa. Floral volatiles from putative hybrid individuals showed a transgressive phenotype, with additional compounds not emitted by either parental species.Our results suggest the presence of a hybrid swarm between sympatric M. pentlandiana and M. laxa and indicate that initial hybridization events between these parental species are rare, but once they occur, visits between putative hybrids and M. laxa are common and facilitate continued introgression.